A study on the relationship between high school students’ sleep quality, physical exercise, academic stress, and subjective well-being - Ruirui Cheng; Lei Yang; Suh-Jung Kang (BMC Psychology)
Abstract Objective This Research explores the intermediary function of academic stress and sleep quality in the connection between physical exercise and subjective well-being among high school students. Methods This Research conducted an online survey through random sampling with a sample of 540 (males = 310, females = 217; grade 10 = 159, grade 11 = 190, grade 12 = 178) high school students to explore the intermediary function of academic stress and sleep quality between physical exercise and subjective well-being. The participants were surveyed using PSQI, the Subjective Well-Being Scale, the ESSA, and PSQI. SPSS Statistics 26 was used to conduct reliability and validity tests, descriptive statistics, and correlation analysis. Mediation analysis was conducted utilizing Model 6 from the PROCESS 4.0 plugin. Results (1) Physical exercise shows a significant positive correlation with subjective well-being, and the direct impact of physical exercise on subjective well-being is also significant. (2) Physical exercise adversely affects academic stress and positively influences sleep quality. Academic stress negatively impacts sleep quality and subjective well-being, while sleep quality positively influences subjective well-being. (3) Academic stress and sleep quality serve as significant mediators between physical exercise and subjective well-being. The mediation effect encompasses two indirect paths: In one aspect, physical exercise has an indirect impact on subjective well-being through its influence on academic stress; in another aspect, physical exercise indirectly affects subjective well-being via the chain mediation effects of academic stress and sleep quality. Conclusion Physical exercise can directly influence the subjective well-being of high school students. Additionally, physical exercise can indirectly impact their subjective well-being through academic stress, and it can also indirectly influence their subjective well-being through the chain mediation effect of academic stress and sleep quality. Based on these findings, it is recommended that schools provide more opportunities for physical exercise, integrated with psychological counseling and sleep management, to help students effectively alleviate academic stress, thereby enhancing their overall well-being.